A Null Mutation of TNFRSF11A Causes Dysosteosclerosis, Not Osteopetrosis - Kırkgöz, Tarık; Özkan, Behzat; Hazan, Filiz; Acar, Sezer; Nalbantoğlu, Özlem; Özkaya, Beyhan; Kulalı, Melike Ataseven; Gürsoy, Semra; Ikegawa, Shiro; Guo, Long (Frontiers in Genetics, 2022)
Dysosteosclerosis (DOS) is a rare sclerosing bone dysplasia characterized by unique osteosclerosis of the long tubular bones and platyspondyly. DOS is inherited in an autosomal recessive manner and is genetically and clinically heterogeneous. To date, four individuals with DOS who have five different TNFRSF11A mutations have been reported. Based on their data, it is hypothesized that mutations producing aberrant mutant RANK proteins (missense or truncated or elongated) cause DOS, while null mutations lead to osteopetrosis, autosomal recessive 7 (OPTB7). Herein, we present the fifth case of TNFRSF11A-associated DOS with a novel homozygous frame-shift mutation (c.19_31del; p.[Arg7CysfsTer172]). The mutation is predicted to cause nonsense mutation-mediated mRNA decay (NMD) in all RANK isoform transcripts, resulting in totally null allele. Our findings suggest genotype-phenotype relationship in TNFRSF11A-associated OPTB7 and DOS remains unclear, and that the deficiency of TNFRSF11A functions might cause DOS, rather than osteopetrosis. More data are necessary to understand the phenotypic spectrum caused by TNFRSF11A mutations.